Enhancing Stamped Part Quality: Real-Time Split Detection Using the ARGUS System to Eliminate Panel Waste - Patel, Kevin (International Journal of Scientific Research and Management (IJSRM), 2024)
High-strength sheet metal stamping, especially with Advanced High-Strength Steels (AHSS) like SCGA1180 (galvannealed 1180 MPa steel), faces significant formability challenges. A primary failure mode is splitting, where localized necking leads to cracks in formed panels. Ensuring quality in mass production is difficult due to limited real-time feedback in traditional stamping lines. This paper proposes an integrated approach using the ARGUS 3D optical forming analysis system for real-time split detection, in conjunction with AutoForm® stamping simulations, to proactively identify and eliminate splits. We provide a comprehensive introduction to stamping challenges with AHSS, including material formability limits and typical failure modes. A detailed technical overview of the ARGUS system is presented – covering its operating principle based on photogrammetry and dot-grid strain measurement, real-time data acquisition of full-field strains, and how it compares measured strains against Forming Limit Curves (FLCs) to flag critical areas. We then describe a methodology for integrating ARGUS in production stamping lines, using simulation predictions from AutoForm to focus monitoring on high-risk zones and enable prompt corrective actions (e.g. press adjustments or tool modifications) before producing excessive scrap. A case study on an automotive B-pillar inner panel made of SCGA1180 steel is presented, where ARGUS detected an incipient split in real time. The case study includes measured major/minor strain distributions, thickness reduction maps, and forming limit diagrams with and without the ARGUS-based intervention. We show that by comparing ARGUS measurements with simulation predictions, the stamping process was optimized to reduce peak strain from ~35% to ~25% (below the FLC), eliminating panel splits. Quantitative results include stress–strain data, forming limit diagram analysis, and a reduction of scrap rate from 5% of panels to essentially zero. Three tables detail material properties of SCGA1180 vs. conventional steels, simulation vs. measurement strain values at critical locations, and production quality metrics before and after ARGUS implementation. Five figures (including color-coded strain maps, FLC charts, and ARGUS integration schematics) and three illustrative graphs (e.g. strain vs. position along the panel) supplement the analysis. The findings demonstrate that real-time forming analysis with ARGUS, when integrated with upfront simulation, can significantly enhance stamped part quality, prevent splits, and eliminate unnecessary panel waste. The paper concludes with implications for Industry 4.0 quality control in stamping and recommendations for broader implementation of optical strain monitoring to achieve zero-defect manufacturing.